Lipase-catalyzed purification and functionalization of Omega-3 polyunsaturated fatty acids and production of structured lipids - Casas Godoy, Leticia (HAL CCSD, 2012)
Lipases are enzymes with applications extended to a wide variety of industries. The variety of lipases applications led to increased research to characterize them and better understand their kinetics and reaction mechanisms and to establish methods for lipase production in homologous and heterologous expression systems. Lately enzymatic engineering allowed the improvement of lipase characteristics. This thesis project studies the use of lipases for two main objectives: lipase-catalyzed purification and functionalization of Omega-3 polyunsaturated fatty acids (PUFAs), especially cis-4, 7, 10, 13, 16, 19-docosahexaenoic acid (DHA) and production of structured lipids (SL). DHA was used for the synthesis of a pharmaceutical molecule, the nicotinyl DHA ester. The co-substrate of the reaction was nicotinol, an alcohol from the group B pro-vitamin, which after absorption is rapidly converted into nicotinic acid (Vitamin B3). The enzymatic trans-esterification of DHA ethyl esters with nicotinol was optimised to synthesise an ester presenting the cumulative properties of the two reactants. After enzyme (immobilized lipase from Candida antarctica; Novozym 435) and reaction medium (solvent-free system) selection, the process was optimised. A conversion to nicotinyl-DHA superior to 97 % was obtained in 4 hours using 45 g.L-1 of enzyme. With a productivity of 4.2 g of product .h-1.g of enzyme-1.This project requires DHA of high purity. Enzymatic purification was chosen for the production of DHA concentrates. Lipases can discriminate between fatty acids in function of their chain length and saturation degree. Lipases react more efficiently with the bulk of saturated and mono-unsaturated fatty acids than with the PUFAs. The objective was the discovery of more specific enzymes for DHA purification. The lipase Lip2 from Yarrowia lipolytica (YLL2) appears as a good candidate since it is homologous to one of the most efficient lipase, the lipase from Thermomyces lanuginosus. YLL2 enables a high discrimination to be obtained, ...